Inside Back Cover: Twisting of Porphyrin by Assembly in a Metal‐Organic Framework yielding Chiral Photoconducting Films for Circularly‐Polarized‐Light Detection (Angew. Chem. Int. Ed. 10/2023). Issue 10 (10th February 2023) - Li, Chun; Schopmans, Henrik; Langer, Lukas; Marschner, Stefan; Chandresh, Abhinav; Bürck, Jochen; Tsuchiya, Youichi; Chihaya, Adachi; Wenzel, Wolfgang; Bräse, Stefan; Kozlowska, Mariana; Heinke, Lars
Abstract : A chiral metal‐organic framework film with optoelectronic properties based on functionalized porphyrin molecules is presented by Mariana Kozlowska, Lars Heinke et al. in their Research Article (e202217377) . While the porphyrin molecules in solution (red) are planar, as common porphyrin, the porphyrin cores are twisted and chiral upon assembly in the metal‐organic framework. The close packing and the crystalline order of the porphyrin cores in the film result in excellent photoconduction properties and sensitivity to circularly polarized light.